2020
DOI: 10.1063/5.0023887
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamics in rubrene and its spectroscopic manifestation

Abstract: A multimode Brownian oscillator model is employed to investigate absorption line shapes of rubrene in solution and thin film. Excellent agreement has been obtained between simulated and measured absorption spectra. Furthermore, using parameters obtained from fitting absorption spectra of rubrene, dynamics of singlet fission is explored by the Dirac-Frenkel time-dependent variation with multiple Davydov trial states. By comparing the absorption spectra between a conical intersection model and the multimode Brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Since an arbitrary nuclear wave function can be expanded as a linear combination of time-dependent coherent states, the Gaussian basis methods can in principle achieve a formally exact description of quantum dynamics once the Gaussian basis is sufficiently expanded toward completeness. Typical approaches using time-dependent Gaussian basis functions include the multiple spawning (MS) method [21,22], the coupled coherent states (CCS) [23,24], the multiconfigurational Ehrenfest (MCE) method [25,26], the methods of variational Multiconfigurational Gaussians (vMCG) [27], the hierarchy of the Davydov ansätze (DA) [28][29][30][31][32][33], and the Gaussian-based multiconfiguration time-dependent Hartree (G-MCTDH) method [34]. It has been shown that the Gaussian basis method with the center of each Gaussian moving along the classical trajectory already yields accurate spectra of time-resolved stimulated emission in molecular systems if sufficient Gaussians are included [35].…”
Section: Introductionmentioning
confidence: 99%
“…Since an arbitrary nuclear wave function can be expanded as a linear combination of time-dependent coherent states, the Gaussian basis methods can in principle achieve a formally exact description of quantum dynamics once the Gaussian basis is sufficiently expanded toward completeness. Typical approaches using time-dependent Gaussian basis functions include the multiple spawning (MS) method [21,22], the coupled coherent states (CCS) [23,24], the multiconfigurational Ehrenfest (MCE) method [25,26], the methods of variational Multiconfigurational Gaussians (vMCG) [27], the hierarchy of the Davydov ansätze (DA) [28][29][30][31][32][33], and the Gaussian-based multiconfiguration time-dependent Hartree (G-MCTDH) method [34]. It has been shown that the Gaussian basis method with the center of each Gaussian moving along the classical trajectory already yields accurate spectra of time-resolved stimulated emission in molecular systems if sufficient Gaussians are included [35].…”
Section: Introductionmentioning
confidence: 99%
“…The off-diagonal elements representing the interaction between the ground and excited state are ∆ 12 = ∆ 21 = 0.32ω. It should be noted that, while similar single crystals, which include rubrene 52,53 and pentacene 54 have been modeled and investigated, the parameter values of the offdiagonal element of tetracene has not been well explored. Here we employ the value of pentacene as a representative case, while the interactions between the excited states are chosen to be ∆ 23 = ∆ 32 = 1.23ω for the pair 1 and ∆ 23 = ∆ 32 = 0.12ω for the pair 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 Based on many-body wave functions, the multiple Davydov Ansatz method is nonperturbative and numerically exact if provided sufficiently large multiplicities of the trial states, capable to compute nonlinear spectroscopic responses for close comparisons with experiment as will be elaborated in the next section. 52,127…”
Section: àπmentioning
confidence: 99%
“…Without the contribution of excited-state absorption, the PE third polarization P 3 ð Þ t ð Þ can be decomposed into four nonlinear response functions R 1À4 , which form the theoretical bases for the simulation of various 2D spectra. 4,6 The third-order response is directly given by the response functions in the impulsive limit, which can be expressed through the multi-D 2 parameters in Equation ( 18) as follows 27,52,59,104 :…”
Section: Spectral Simulation Via Davydov's Ansätzementioning
confidence: 99%
See 1 more Smart Citation